Turkey : Evaluating the Impact of Iskur's Vocational Training Programs - World Bank (2014)
Turkey's economic performance during the 2000s is a global success story; high-income status is now within reach but this will require creating more and better jobs. Upgrading the skills of the current labor force is crucial for creating more and better jobs. The Turkish Employment Agency (ISKUR) plays a leading role in upgrading the skills of jobseekers and facilitating their access to productive employment by providing vocational training and other employment support services. The increasing importance of ISKUR vocational training prompted the government to commission the present study to evaluate its impact and to identify ways to enhance it. The study evaluates the main type of ISKUR's vocational training courses at a particular point in time, and thus it does not take into account recent reforms. The study evaluates a representative sample of general vocational training courses, which account for about two thirds of ISKUR vocational trainees (the other one-third mostly take courses on demand by employers) that took place between December 2010 and June 2011. The evaluation has an experimental design, exploiting the excess demand for ISKUR vocational training courses to randomly assign eligible training applicants into those who receive training (treatment group) and those who do not (control group). The study makes use of the findings from this evaluation, complemented by evidence from other countries, to suggest a number of policy options to further strengthen the impact of ISKUR training and services. In this context, this report is structured as follows: section one gives the context: jobs, skills upgrading, and ISKUR; section two presents evaluation of ISKUR training programs: design, data, and methods; section three presents evaluation of ISKUR training programs: results; and section four gives strengthening the impact of ISKUR training and services.